Layar Merapi: Encouraging disaster preparedness through open-air cinema initiatives in Dukun Subdistrict - Arifianto, Budi Dwi; Utami, Citra Dewi; Muktaf, Zein Mufarih (Universitas Muhammadiyah Magelang, 2025)
Dukun Subdistrict is one of the areas with a high level of vulnerability to Mount Merapi eruptions. The low understanding of technical disaster mitigation terms among rural communities, particularly those in the KRB III (Third Zone of Disaster-Prone Area), served as the foundation for implementing the